Poly (Lactic Acid): An Eco-Friendly Biodegradable Polymer - Satya Lakshmi S; Vineela N; Srinivasa Rao Y; Kamala Kumari P V (Journal of Global Pharma Technology, 2021)
Poly (lactic acid) or poly (lactide) (PLA) is bio-based, renewable and biodegradable aliphatic thermoplastic polyester. Lactic acid is synthesized industrially either by biological or chemical route. For the production of lactic acid biological method is mostly preferred as it gives optically pure lactic acid. PLA could be a technical and economical alternative to the problem of eventual disposal of very large amount of plastic packaging worldwide. A summarized description is given regarding the physical, thermal, mechanical properties, technologies for PLA production, synthesis of poly (lactic acid) (PLA) from its monomer, poly blends and finally the biomedical applications discussed here. Keywords: PLA (lactic acid), Poly blends, Polycondensation, Fermentation, Lactide, Oligomers.